PENGARUH PENGALAMAN MAGANG TERHADAP KESIAPAN KERJA FRESH GRADUATES FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS PADJADJARAN - Nazhira Putri; Wa Ode Zusnita Muizu (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
Along with the development of the world of education in Indonesia, this shows that the education sector is Along with the development of the world of education in Indonesia, this shows that the education sector is receiving more attention from the government, including higher education levels. Starting from academic programs that are formed in such a way as internships, volunteers, etc. with the aim of increasing the readiness of both students and graduates (fresh graduates) to enter the professional world so as to improve the quality of human resources in Indonesia. But in fact there are still a number of university graduates who are unemployed because the industry considers that university graduates are still not ready to face the world of work which is supported by data that the work readiness of high level graduates in Indonesia is only 10% which can be caused by inadequate abilities and job demands. . So this research aims to find out how internships influence students' preparation for entering the world of work. Respondents in this research were 131 graduates of the Faculty of Economics and Business from undergraduate study programs in Accounting, Economics, Management, Islamic Economics and Digital Business, FEB, Padjadjaran University with SmartPLS version 4 data processing. Based on research findings, 36% internship experience can simultaneously increase job readiness of fresh graduates. Meanwhile, as much as 64% was influenced by variables not examined in this research.